The Role of T Helper (TH)17 Cells as a Double-Edged Sword in the Interplay of Infection and Autoimmunity with a Focus on Xenobiotic-Induced Immunomodulation - Nasr Y. A. Hemdan; Ahmed M. Abu El-Saad; Ulrich Sack (Clinical and Developmental Immunology)
Extensive research in recent years suggests that exposure to xenobiotic stimuli plays a critical role in autoimmunity induction and severity and that the resulting response would be exacerbated in individuals with an infection-aroused immune system. In this context, heavy metals constitute a prominent category of xenobiotic substances, known to alter divergent immune cell responses in accidentally and occupationally exposed individuals, thereby increasing the susceptibility to autoimmunity and cancer, especially when accompanied by inflammation-triggered persistent sensitization. This perception is learned from experimental models of infection and epidemiologic studies and clearly underscores the interplay of exposure to such immunomodulatory elements with pre- or postexposure infectious events. Further, the TH17 cell subset, known to be associated with a growing list of autoimmune manifestations, may be the “superstar” at the interface of xenobiotic exposure and autoimmunity. In this review, the most recently established links to this nomination are short-listed to create a framework to better understand new insights into TH17’s contributions to autoimmunity.